APPLYING THE ISLAMIC LAW FROM THE VIEWPOINT OF MAQASHID AL-SHARIAH: ANALYZING LEGAL OPINIONS OF SRI LANKAN MUSLIM SCHOLARS - Shihan, Mohammad; Zaroum, Abdulhamid Mohamed Ali (Asy-Syari'ah, 2022)
Abstract: The SharÄ«Ê¿ah is of fundamental importance for all Muslims. No Muslim is exempted from following the SharÄ«Ê¿ah. However, the understanding of Islamic law is often too narrow and problematic for several reasons. Further, this situation is more critical in the Muslim minority context since it paves the ways to misunderstand and misinterpret the nature and purpose of the SharÄ«Ê¿ah. Therefore, applying SharÄ«Ê¿ah Â has become a controversial matter that harms peopleâ€™s interests rather than serves them. Further, during the last few decades, there has been significant interest among the scholars of SharÄ«â€™ah in producing the MaqÄsid al-SharÄ«â€™ah as a new methodology to interpret the texts of SharÄ«Ê¿ah.Â  They propose MaqÄsid al-SharÄ«â€™ah as general principles that open expansive rooms for applying SharÄ«Ê¿ah under its broad perspective. Acknowledging this background, the researcher examined the views of Sri Lankan Muslim scholars about applying SharÄ«Ê¿ah based on MaqÄsid al-SharÄ«â€™ahâ€™s viewpoint. Hence, the perceptions about the application of SharÄ«Ê¿ah are collected from selected Muslim scholars by conducting the interview. This study follows the qualitative method of data collection and content analysis method to reach the results and findings. Accordingly, the study reveals that the prevailing narrow perspective about SharÄ«Ê¿ah serves as an obstacle for the correct and beneficial application of the SharÄ«Ê¿ah and causes negative perceptions among the public. Consequently, the study concludes that the broad perspective of SharÄ«â€™ah opens a more expansive space for the application of SharÄ«â€™ah and largely helps cooperate and collaborate with other religious communities.